Pneumocystis jirovecii pneumonia in tropical and low and middle income countries: a systematic review and meta-regression. - David M Lowe; Molebogeng X Rangaka; Fabiana Gordon; Chris D James; Robert F Miller (PLoS ONE)
Objective Pneumocystis jirovecii pneumonia (PCP), the commonest opportunistic infection in HIV-infected patients in the developed world, is less commonly described in tropical and low and middle income countries (LMIC). We sought to investigate predictors of PCP in these settings. Design Systematic review and meta-regression. Methods Meta-regression of predictors of PCP diagnosis (33 studies). Qualitative and quantitative assessment of recorded CD4 counts, receipt of prophylaxis and antiretrovirals, sensitivity and specificity of clinical signs and symptoms for PCP, co-infection with other pathogens, and case fatality (117 studies). Results The most significant predictor of PCP was per capita Gross Domestic Product, which showed strong linear association with odds of PCP diagnosis (p<0.0001). This was not explained by study design or diagnostic quality. Geographical area, population age, study setting and year of study also contributed to risk of PCP. Co-infection was common (444 episodes/1425 PCP cases), frequently with virulent organisms. The predictive value of symptoms, signs or simple tests in LMIC settings for diagnosis of PCP was poor. Case fatality was >30%; treatment was largely appropriate. Prophylaxis appeared to reduce the risk for development of PCP, however 24% of children with PCP were receiving prophylaxis. CD4 counts at presentation with PCP were usually <200×10(3/)ml. Conclusions There is a positive relationship between GDP and risk of PCP diagnosis. Although failure to diagnose infection in poorer countries may contribute to this, we also hypothesise that poverty exposes at-risk patients to a wide range of infections and that the relatively non-pathogenic P. jirovecii is therefore under-represented. As LMIC develop economically they eliminate the conditions underlying transmission of virulent infection: P. jirovecii, ubiquitous in all settings, then becomes a greater relative threat.